Komunikace mezi člověkem a papouškem šedým - Tymr, František (Lidé města, 2004)
Goal of the first experiment has been to learn whether the Model/Rival learning technique is applicable for the individuals from wild living conditions that have used a natural parrot vocalization and who has contacts with other parrots during the experiment. During 5 month learning session that were five days a week, 15-30 min several times per day it had not been noticed any use of human words by parrots. After that another parrot that is able to use 15 human words was included into the experiment. Parrots were left alone for first two days. During these days the first parrot had learned one human word from "speaking" individual. There has not been recorded clear evidence till now when the target individual (a wild parrot) has learned any human word by the Model/Rival technique. He only uses expressions commonly used and learned by the second parrot. There is no word for the marking of a concrete object. The learned words were simply added to natural vocalisation. The second experiment goal was to study factors that influence learning abilities of Gray parrots (sex of a teacher, time and parrot speaking preferences). The words were analogical by a sound set and a length of a word; changes were made by the shifting of syllables. The parrot has learned five new words (from the selected set) during 93,5 hours of learning that have been 254 times repeated.